Evaluating the Antagonistic Potential of Actinomycete Strains Isolated From Sudan’s Soils Against Phytophthora infestans - Abdelrahman, Ola; Yagi, Sakina; El Siddig, Marmar; El Hussein, Adil; Germanier, Fanny; De Vrieze, Mout; L’Haridon, Floriane; Weisskopf, Laure (Frontiers in Microbiology, 2022)
Soil microorganisms play crucial roles in soil fertility, e.g., through decomposing organic matter, cycling nutrients or through beneficial interactions with plants. Actinomycetes are a major component of soil inhabitants; they are prolific producers of specialized metabolites, among which many antibiotics. Here we report the isolation and characterization of 175 Actinomycetes from rhizosphere and bulk soil samples collected in 18 locations in Sudan. We evaluated the strains’ metabolic potential for plant protection by testing their ability to inhibit the mycelial growth of the oomycete Phytophthora infestans, which is one of the most devastating plant pathogens worldwide. Most strains significantly reduced the oomycete’s growth in direct confrontational in vitro assays. A significant proportion of the tested strains (15%) were able to inhibit P. infestans to more than 80%, 23% to 50-80%, while the remaining 62 % had inhibition percentages lesser than 50%. Different morphologies of P. infestans mycelial growth and sporangia formation were observed upon co-inoculation with some of the Actinomycetes isolates, such as the production of fewer, thinner hyphae without sporangia leading to a faint growth morphology, or on the contrary, of clusters of thick-walled hyphae leading to a bushy, or “frozen” morphology. These morphologies were caused by strains differing in activity levels but phylogenetically closely related with each other. To evaluate whether the isolated Actinomycetes could also inhibit the pathogen’s growth in planta, the most active strains were tested for their ability to restrict disease progress in leaf disc and full plant assays. Five of the active strains showed highly significant protection of potato leaves against the pathogen in leaf disc assays, as well as substantial reduction of disease progress in full plants assays. Using cell-free filtrates instead of the bacterial spores also led to full protection against disease on leaf discs, which highlights the strong crop protective potential of the secreted metabolites that could be applied as leaf spray. This study demonstrates the strong anti-oomycete activity of soil- and rhizosphere-borne Actinomycetes and highlights their significant potential for the development of sustainable solutions based on either cell suspensions or cell-free filtrates to safeguard potatoes from their most damaging pathogen.